Government Foreign Debt and Macroeconomic Stability in Indonesia - La Ode Suriadi; Rostin Rostin; Andriani Puspitaningsih; Surianti; Puspa Dewangga (Universitas Negeri Semarang, 2026)
This study examines the short- and long-run relationships between Government Foreign Debt (GFD) and Indonesia’s macroeconomic stability using the Vector Error Correction Model (VECM) and annual time-series data covering the period 1995–2024. The analysis incorporates five key variables: Government Foreign Debt (GFD), inflation, economic growth, the exchange rate, and investment. Data were obtained from Statistics Indonesia (BPS), Bank Indonesia, the Ministry of Finance, and relevant international publications. The VECM framework was employed following unit root and cointegration tests to capture both the long-run equilibrium relationships and the short-run dynamic adjustments among the variables. The estimation results indicate that GFD exerts significant long-run effects by increasing inflation, depreciating the exchange rate, and constraining economic growth. In the short run, however, its effects are more limited, although debt-financed fiscal spending may provide temporary support for economic activity. The Impulse Response Function (IRF) analysis further shows that shocks to GFD generate negative responses in economic growth and investment while increasing inflation and causing exchange rate depreciation. Variance Decomposition (VD) results demonstrate that the contribution of GFD to fluctuations in economic growth, inflation, and the exchange rate becomes increasingly substantial over time. Overall, the findings suggest that Government Foreign Debt plays a critical yet potentially risky role in maintaining macroeconomic stability. Therefore, prudent debt management should prioritize productive long-term financing to minimize external vulnerabilities, maintain fiscal sustainability, and strengthen long-term macroeconomic stability